Farm-managers or unpaid laborers? Women farmers in male-headed households of Central India - Krishna, Vijesh V.; Khed, Vijayalaxmi D.; Gartaula, Hom Nath; Badstue, Lone (International Maize and Wheat Improvement Center, 2023)
In the context of agricultural research and development (AR&D) in the global South, there is a growing recognition of the role of women farmers and the relevance of targeting them. The level of women’s participation in agricultural activities is influenced by factors such as male outmigration from the agricultural sector, and prevailing social norms. This participation varies both temporally and spatially, thereby influencing the strategies for targeted technology development and dissemination. This empirical study draws farmhousehold survey data from eastern Madhya Pradesh, India, where the rate of male outmigration from agriculture has been marginal. The objective is to assess the relationship between the involvement of women in labor provision and decision-making in wheat production. The findings reveal variations in women’s roles and their extent of participation in different agricultural activities. Concerning access to credit and soil fertility management, women are predominantly categorized as nonparticipants. Conversely, women commonly engage in weeding, irrigation, and harvesting activities, but their roles are typically limited to ‘unpaid family labor.’ Only in postharvest operations do women actively participate in labor provision while having decision-making power comparable to that of men, thus approaching the function of ‘farm managers.’ It is important to note that women’s active involvement in agricultural decision-making is closely linked to their participation in decision-making within other domains as well. By recognizing and promoting women’s participation in decision-making processes, AR&D programs can foster inclusive and sustainable agricultural development.